Diluted Magnetic Semiconductor Effects in Mn- and Fe-Implanted Silicon Carbide - Komarov, A.V.; Los, A.V.; Ryabchenko, S.M.; Romanenko, S.M. (Ukrainian Journal of Physics, 2022)
Light transmission and Faraday rotation spectra measured at a temperature of 2 K for 4H–SiC and 6H–SiC single crystals of silicon carbide implanted with Mn and Fe ions, respectively, and for control specimens of the same single crystals not subjected to the implantation have been compared. A 190 keV beam is used to implant ions at the total exposure doses of 3.8 × 1016 and 5.5 × 1016 cm–2. As a result, layers of about 0.2 μm in thickness doped with Mn or Fe ions to the average ionic concentration of about 1021 cm–3 emerged. Although the light transmission through implanted crystals is only slightly changed in comparison with that for the reference specimen, it corresponds to rather a high value of the light extinction coefficient in the implanted layer. Such a phenomenon is interpreted as a result of the light scattering by optical inhomogeneities created by high-energy ions in the surface layer. The presence of magnetic ions in the near-surface layer gives rise to noticeable changes in the Faraday rotation spectra of specimens. The estimated values of the Verdet constant for those layers turn out of the opposite sign and about three orders of magnitude larger than that for the undoped specimens. The dependences of the Faraday rotation contribution on the magnetic field for the Mn-implanted layer are found to get saturated, which evidences a proportionality between the Faraday rotation and the magnetization of the paramagnetic subsystem of Mn ions. In the case of a Fe-implanted layer, those dependences turn out linear, similar to what is observed for AIIFeBIV semimagnetic semiconductors. An assumption is made that Fe ions are in the singlet ground state in SiC and AIIFeBIV and become magnetized in an external field owing to a mechanism similar to the van Vleck one. The SiC layers with implanted Mn or Fe ions are found to reveal magnetooptical properties typical of diluted magnetic (semimagnetic) semiconductors. At the same time, no ferromagnetic ordering is observed in the studied (Si,Mn)C and (Si,Fe)C specimens.